Regional urban-rural distribution of dental caries experience in Swaziland - Gugushe, T S; du Plessis, J B (SADJ (Houghton), 1998)
Understanding the regional and countrywide urban-rural distribution of dental caries in Swaziland was considered important for the formulation of a National Oral Health Policy based on the Primary Health Care Approach. A National Oral Health survey was undertaken in Swaziland at the request of the ministry of health. Part of the objective of this study was to establish the regional urban-rural distribution of dental caries in Swaziland. For the 6-18 year olds a cluster sampling technique by schools was used to get a representative sample. For the 35-44 year age group a simple random sampling technique was used in areas of employment influenced by regional and urban-rural distribution. All examinations were carried out using the WHO 1987 criteria. More than 90 per cent of the mean dmft of 6 and 12 year olds was comprised of the decayed component of the dmft/DMFT. The level of restorative care (ft/dmft, FT/DMFT) was low for all age groups. For the 6 and 12 year olds in the Lubombo region there was a significant difference (p < 0.05) in the urban-rural caries experience. When regional data for 6 and 12 year olds were pooled, the difference in urban-rural caries experience is also significant (p < 0.05). For the older age groups there was no significant difference (p > 0.05) in the regional urban-rural caries experience. This study indicates that the oral health care system in Swaziland with its limited resources, should focus its attention on the younger age groups especially in urban areas as far as dental caries treatment needs and preventive programmes are concerned.